The effect of transforaminal epidural steroid injections in patients with spondylolisthesis - (:unkn) unknown (IOS PRESS, 2017)
BACKGROUND: Transforaminal epidural steroid injection (TFE) is a widely accepted non-surgical treatment for pain in patients with spondylolisthesis. However, the effectiveness of TFE has not been compared in patients with degenerative (DS) and isthmic spondylolisthesis (IS). OBJECTIVE: To compare the effectiveness of bilateral TFEs in DS and IS. METHODS: Patients who underwent bilateral TFEs for spondylolisthesis at University of California San Francisco Orthopaedic Institute from 2009 to 2014 were evaluated retrospectively. RESULTS: DS patients (120 female, 51 male) were significantly older and had higher comorbidity than those with IS (18 female, 14 male). They had better pain relief after TFE than patients with IS (72.11 +/- 27.46% vs 54.39 +/- 34.31%; p = 0.009). The number of TFEs, the mean duration of pain relief after TFE, follow-up periods, translation and facet joint widening were similar in DS and IS groups (p > 0.05). DS group had higher successful treatment rate (66.1% vs 46.9%, p = 0.009) and longer duration of pain relief (181.29 +/- 241.37 vs 140.07 +/- 183.62 days, p = 0.065) compared to IS group. CONCLUSIONS: Bilateral TFEs at the level of spondylolisthesis effectively decreased pain in patients. TFEs provided better pain relief for longer duration in patients with DS than for those with IS.
Keywords: Degenerative spondylolisthesis; isthmic spondylolisthesis; transforaminal epidural steroid injection; pain relief; co-morbidity scores; LUMBAR DISC HERNIATION; LOW-BACK-PAIN; NERVE ROOT BLOCKS; RADICULAR PAIN; SPINAL STENOSIS; DEGENERATIVE SPONDYLOLISTHESIS; OUTCOME PREDICTORS; DOUBLE-BLIND; SCIATICA; RADICULOPATHY